Implementasi Failure Mode Effect Analysis (FMEA) dan Fuzzy Logic sebagai Program Pengendalian Kualitas - Siti Aisyah (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
PT SKF Indonesia which is one of the largest manufacturing companies in Indonesia produced various types of Bearing 6201. There are many failures in the production process that reduces the function of Bearing. To be able to meet consumer desires and to prevent or eliminate failures, companies need to make improvement programs that can minimize the failure rate which is the implementation of Failure Mode and Effect Analysis (FMEA) and the use of fuzzy logic. The purpose of this study is to analyze the proportion of defects and process capability in assembly, analyzing potential failures, identify root causes of defects, and calculate the value of the highest RPN. In addition, to create improvement plans based on the highest RPN. The data used based on data occurred during October 2010. Based on the data processing using fuzzy FMEA method, found that the failure rate of occurrence of defects per day amounted to 1.005%. For the Cp value is equal to 1.29 and Cpk of 1.22. Types of failures that occur in the process are Noise, Shoemark, Black Surface and Wedge. RPN values obtained from the results using conventional methods and fuzzy FMEA is basically the same. From the results obtained the highest ranking RPN calculation for this type of failure Noise. To seek improvements in the quality of disability Noise, prepared improvement plans using 5W-1H for the human, material, environment, methods, and machinery. Improvement plans to minimize the amount of noise is to give training to the employees. There is need for the inspection process by sampling the incoming raw materials to add lights at points that are important in the production room, always pay attention when the lamp is die and replace it with a new, in the preparation of OR and IR components must be aligned, sticking posters in the work area that contains the image the correct way up, schedule an examination 1 week once the machine is known engine or not feasible to use, and optimize preventive maintenance.Keywords: Failure Process, Failure Mode and Effect Analysis, Fuzzy Logic, Fuzzy FMEA, RPN